Lyme disease associated neurological and musculoskeletal symptoms: A systematic review and meta-analysis - Ganesh Bushi; Ashok Kumar Balaraman; Shilpa Gaidhane; Suhas Ballal; Sanjay Kumar; Mahakshit Bhat; Shilpa Sharma; M Ravi Kumar; Aashna Sinha; Mahalaqua Nazli Khatib; Nishant Rai; Sanjit Sah; et al. (Brain, Behavior, & Immunity - Health)
Background and objective: Lyme disease, caused by Borrelia burgdorferi, presents major health challenges worldwide, leading to serious neurological and musculoskeletal issues that impact patients' lives and healthcare systems. This systematic review and meta-analysis aim to determine the prevalence and link between Lyme disease and these complications, aiming to enhance clinical and public health approaches. Methods: We systematically searched PubMed, EMBASE, and Web of Science up until April 01, 2024, to find studies reporting the prevalence and severity of neurological and musculoskeletal complications associated with Lyme disease. Screening and data extraction were conducted using Nested Knowledge software. Two independent reviewers performed the quality assessment using the Newcastle-Ottawa Scale. Meta-analyses were performed using R software v4.3, employing a random-effects model. Results: Out of 3576 records, 17 studies were included, involving 3932 participants. These studies revealed significant prevalence of musculoskeletal symptoms (21.1%) and neurological disabilities (18%) among Lyme disease patients. The analysis showed a notable increase in risk for both complications in individuals with Lyme disease, with pooled Risk Ratios (RR) of 1.82 for musculoskeletal symptoms and 1.64 for neurological disabilities, indicating a significantly higher risk compared to control groups. Although heterogeneity across the studies was high, sensitivity analysis confirmed the consistency of our findings. Additionally, there was evidence of publication bias. Conclusion: The study reveals significant neurological and musculoskeletal complications in Lyme disease patients, emphasizing the importance of early diagnosis, comprehensive treatment, and supportive care. The noted heterogeneity and potential publication bias highlight the need for transparent research and further study on long-term outcomes.